Alotanypus vittigera (Edwards) comb. nov.: adult redescription, immature description and a phylogenetic analysis of the genus (Diptera: Chironomidae: Tanypodinae) - Siri, Augusto; Donato, Mariano; Orpella, Germán; Massaferro, Julieta (Zootaxa, 2011)
Anatopynia vittigera Edwards is transfered to Alotanypus. The male and female of A. vittigera comb. nov. are redescribed and immatures are described and illustrated. A cladistic analysis including one species of each Macropelopiini genus was conducted in order to assess the phylogenetic position of Alotanypus and to provide the first phylogenetic hypothesis for the genus. Adults and immatures were included in the analysis where discrete and continuos characters were considered. The cladistic analysis demonstrated that Alotanypus is a monophyletic genus, with Guassutanypus oliveirai as the sister group.